2019
DOI: 10.24815/jped.v4i2.12573
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Capital Adequacy Ratio, Net Interest Margin, Loan to Deposit Ratio Dan Non Performing Loan Terhadap Profitabilitas Bank Umum Non Devisa Di Indonesia Periode 2014-2016

Abstract: This study examines the influence Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) toward Profitability for Non-Foreign Exchange Commercial Bank in Indonesia. This study uses empirical data on the directory of Financial Services Authority (Otorita Jasa Keuangan) through non probability sampling that met criteria of the research. There are 17 Banks observed for 3 years quarterly starting from 2014 until 2016. The analytical method using Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
4
0
14
Order By: Relevance
“…It is also in line with the measurement results of the Sharia Supervisory Board. Octaviani et al [19] also found that, based on the results of research from Maisaroh [20], that there is a significant positive relationship between the Equitable Distribution Ratio and the company's profitability, while Profitability has a significant negative effect on earnings management based on the research results of Purnama [21] and Saputra et al, [22]. Thus, it can be concluded that the results of this study are in line and indirectly consistent with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…It is also in line with the measurement results of the Sharia Supervisory Board. Octaviani et al [19] also found that, based on the results of research from Maisaroh [20], that there is a significant positive relationship between the Equitable Distribution Ratio and the company's profitability, while Profitability has a significant negative effect on earnings management based on the research results of Purnama [21] and Saputra et al, [22]. Thus, it can be concluded that the results of this study are in line and indirectly consistent with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian terdahulu berikutnya (Sagala, et al, 2019) juga menyimpulkan bahwa CAR berpengaruh positif terhadap ROA. Namun bertentangan dengan penelitian (Saputra, et al, 2018) menyimpulkan bahwa CAR tidak berpengaruh terhadap ROA.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini juga tidak sesuai dengan anticipated income theory. Tidak adanya pengaruh NPL terhadap profitabilitas dapat diakibatkan adanya kredit kurang lancar atau macet yang nilainya sangat tinggi akan membuat bank tidak mau menyalurkan kredit disebabkan adanya kondisi dimana bank wajib mempersiapkan cadangan dana yang cukup besar dalam pembiayaan kredit bermasalah tersebut yang kemudian membuat bank akan berhati-hati ketika menyalurkan kreditnya (Saputra et al, 2018). Selain itu, kredit bermasalah seperti kredit kurang lancar atau macet dapat terjadi setiap tahun sehingga tidak ada suatu keadaan yang pasti terkait kenaikan atau penurunan NPL yang disertai pada kenaikan atau penurunan ROA (Apriani & Mansoni, 2019).…”
Section: Tabel 5 Hasil Uji Autokorelasiunclassified
“…Hasil penelitian ini tidak sesuai dengan anticipated income theory. Belum maksimalnya penyaluran kredit yang dilakukan bank ke masyarakat juga menjadi faktor mengapa LDR tidak memiliki pengaruh terhadap profitabilitas bank (Saputra et al, 2018). Hasil penelitian ini tidak mendukung penelitian sebelumnya yang menemukan bahwa LDR memiliki pengaruh positif signifikan terhadap profitabilitas bank (Ambarawati & Abundanti, 2018;Pertiwi & Susanto, 2019).…”
Section: Tabel 5 Hasil Uji Autokorelasiunclassified